2022
DOI: 10.3390/nu14214516
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoid Intake in Relation to Colorectal Cancer Risk and Blood Bacterial DNA

Abstract: Flavonoids have been inversely associated to colorectal cancer (CRC) and are plausible intermediaries for the relation among gut microbiome, intestinal permeability and CRC. We analyzed the relation of flavonoid intake with CRC and blood bacterial DNA. We conducted a case–control study in Italy involving 100 incident CRC cases and 200 controls. A valid and reproducible food–frequency questionnaire was used to assess dietary habits and to estimate six flavonoid subclass intakes. We applied qPCR and 16S rRNA gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 54 publications
0
2
0
2
Order By: Relevance
“…Some micronutrients may have an anti-inflammatory role and ameliorated gut microbiota disorder [ 40 ], and may modulate circulating microbiome. For instance, it has been demonstrated that a higher intake of dietary flavonoids reduces the risk of CRC, and influences the composition of blood bacterial DNA [ 41 ]. Unfortunately, in the present study, no food frequency questionnaire was administered to patients; therefore, it was not possible to correlate flavonoid intake with circulating bacterial DNA.…”
Section: Discussionmentioning
confidence: 99%
“…Some micronutrients may have an anti-inflammatory role and ameliorated gut microbiota disorder [ 40 ], and may modulate circulating microbiome. For instance, it has been demonstrated that a higher intake of dietary flavonoids reduces the risk of CRC, and influences the composition of blood bacterial DNA [ 41 ]. Unfortunately, in the present study, no food frequency questionnaire was administered to patients; therefore, it was not possible to correlate flavonoid intake with circulating bacterial DNA.…”
Section: Discussionmentioning
confidence: 99%
“…Em sua meta-análise, Chang 16 obteve como resultado que o consumo de flavonoides, principalmente a quercetina, e a ingestão de flavonas (como apigenina), podem prevenir o risco de câncer de cólon 16 . No estudo de Speciani et al 17 , também se obteve resultados favoráveis do consumo de flavonoides e câncer de cólon. Os resultados foram que a ingestão de antocianidinas e flavonas podem reduzir o risco de CCR 17 .…”
Section: Introductionunclassified
“…No estudo de Speciani et al 17 , também se obteve resultados favoráveis do consumo de flavonoides e câncer de cólon. Os resultados foram que a ingestão de antocianidinas e flavonas podem reduzir o risco de CCR 17 .…”
Section: Introductionunclassified
“…Anthocyanidins are one of the six major categories of flavonoids, and the anthocyanidins consumed in diet are mainly provided by fruits such as berries (9). Anthocyanidins have powerful anti-inflammatory and antioxidant properties, making them useful in the prevention of a variety of chronic diseases, such as eye and kidney complications and many cancer types (10)(11)(12)(13). An increasing number of evidences show that anthocyanidins is related to circulatory disease, and have shown significant lipid-lowering effects in many studies (14,15).…”
Section: Introductionmentioning
confidence: 99%